2004
DOI: 10.1007/s10512-005-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature gas-cooled reactors — energy source for industrial production of hydrogen

Abstract: High-temperature helium-cooled reactors are the best understood nuclear technology that can supply high-temperature heat for thermal processes for producing hydrogen. The GT-MGR reactor -an innovative international modular design of a helium-cooled reactor with a gas-turbine cycle -best meets the requirements for hydrogen production and is proposed as a basis for a nuclear energy source. In this paper, the technical aspects of the proposed application of HTGR as a source of energy for producing hydrogen are an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…The GT-MGR reactor, an innovative international modular design of a helium-cooled reactor with a gas-turbine cycle, meets the requirements for hydrogen production and has been proposed as a basis for a nuclear energy source (Mitenkov et al, 2004). Technical aspects of the proposed HTGR application for producing hydrogen have been analyzed by Mitenkov et al (2004), who determined the required energy parameters for the HTGR for present and future hydrogenproduction technologies. Challenges and additional research needs relating to the HTGR at high helium temperatures are identified.…”
Section: Introductionmentioning
confidence: 99%
“…The GT-MGR reactor, an innovative international modular design of a helium-cooled reactor with a gas-turbine cycle, meets the requirements for hydrogen production and has been proposed as a basis for a nuclear energy source (Mitenkov et al, 2004). Technical aspects of the proposed HTGR application for producing hydrogen have been analyzed by Mitenkov et al (2004), who determined the required energy parameters for the HTGR for present and future hydrogenproduction technologies. Challenges and additional research needs relating to the HTGR at high helium temperatures are identified.…”
Section: Introductionmentioning
confidence: 99%
“…Использование эндотермического процесса разложения природного газа на водород и углерод представляет большой интерес для крупнотоннажного производства водорода за счёт тепловой энергии от таких источников как высокотемпературные газоохлаждаемые ядерные реакторы (ВГТР) [4][5][6] или гелиотермальные системы. Процесс обеспечивает высокую (близкую 100%) степень конверсии углеводородов уже при сравнительно невысоких рабочих температурах (600 о С -1000 о С) и позволяет получать водород фактически в одну стадию.…”
Section: плазменные и плазменно-каталитические технологии переработки углеводородов с получением водородаunclassified
“…Основные объекты исследований: -высокоэффективные электрокатализаторы и электродные материалы на основе наноразмерных (3)(4)(5)(6)…”
Section: перспективные направления деятельности центра в области электрохимической водородной энергетикиunclassified
“…High temperature helium-cooled reactors are the best understood nuclear technology that can supply high temperature heat for thermal processes for producing hydrogen. Nuclear reactor designers became interested in high-temperature helium-cooled reactors more than 40 years ago because of the new possibility for heating the helium at the reactor exit up to 1000°C and the enhanced safety of the reactor (Mitenkov et al, 2004). The synergistic production of hydrogen using fossil fuels and nuclear energy is considered to be extremely advantageous, especially when performed through a recirculation-type membrane reformer (Hori et al, 2005).…”
Section: Application To Nuclear Powermentioning
confidence: 99%